Prognostic significance of laminin, laminin receptor, and bone marrow micrometastases in breast cancer patients: are these markers of aggressive behavior and metastatic potential? - Molino, Annamaria; Pedersini, Rebecca; Micciolo, Rocco; Frisinghelli, Michela; Giovannini, Monica; Pavarana, Michele; Santo, Antonio; Colato, Chiara; Piubello, Quirino; Cetto, Gian Luigi (Applied immunohistochemistry & molecular morphology, 2003)
Laminin is a basement membrane glycoprotein implicated in a large number of biologic activities of cancer progression, many of which are mediated by the presence of the laminin receptor (67LR) on the cell membrane. We studied the correlations of laminin and its receptor with standardized and new prognostic factors (including bone marrow micrometastases) in a series of 112 patients with operable breast cancers. Laminin-positive cells were detected in 60% of the tumors and 67LR-positive cells in 55%; both were present in 35% of the cases. No association was found between laminin or 67LR positivity and pathologic tumor size, pathologic nodal status, grading, Ki-67, estrogen receptor status, progesterone receptor status, or bone marrow micrometastases. The only statistically significant association was with menopausal status and age, with a higher percentage of 67LR-positive tumors among premenopausal and younger patients. The median follow-up was approximately 7 years. The prognosis of disease-free survival was similar in the laminin-positive and laminin-negative subjects but was significantly better in 67LR-negative patients; there were no significant differences in overall survival. The prognostic role of laminin and 67LR in disease-free survival and overall survival varied according to nodal status. In the absence of nodal involvement, the risk of relapse (and death) was greater in the patients who were positive for laminin, 67LR, or both than in those who were negative for laminin, 67LR, or both; in the case of 4 or more involved nodes, the prognostic role of laminin and 67LR was reversed. These results did not change after adjustment for age, menopausal status, tumor status, nodal status, grading, or bone marrow micrometastases.